Safety and efficacy of Correlink™ ABS747 Bacillus subtilis (Bacillus velezensis NRRL B‐67257) as a feed additive for all growing poultry species - Bampidis, Vasileios (EFSA J, 2020)
Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Correlink™ ABS747 Bacillus subtilis (hereafter designated as Correlink™ ABS747) when used as a feed additive for chickens for fattening, turkeys for fattening, chickens reared for laying, turkeys reared for breeding and minor growing poultry species. The product under assessment is based on viable spores of a strain originally identified as Bacillus subtilis, which in the course of the current assessment, was reclassified as Bacillus velezensis NRRL B‐67257. The bacterial species B. velezensis is considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the active agent was established and it does not harbour acquired antimicrobial resistance genes, lacks toxigenic potential and does not have the capacity to produce aminoglycosides. Following the QPS approach to safety assessment, B. velezensis NRRL B‐67257 is presumed safe for the target species, consumers of products derived from animals fed the additive and the environment. Since no concerns are expected from the other components of the additive, Correlink™ ABS747 is also considered safe for the target species, consumers of products derived from animals fed the additive and the environment. Correlink™ ABS747 is not irritant to skin and eyes or a skin sensitiser but is a respiratory sensitiser. The Panel is not in the position to conclude on the efficacy of Correlink™ ABS747 for the target species due to lack of data.